PENGGUNAAN MEDIA TORSO MATA PELAJARAN IPA KELAS V MIMA NU PLIKEN KEMBARAN BANYUMAS - Nuning Ermy Ustantinah (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
The low participation and achievement of students in learning activities in science subjects at MIMA Nu Pliken Kembaran Banyumas research in classroom research during and after learning using media / torso props takes place. With the type of CAR research with a stage that is the existence of a plan and then carried out, the activities were observed and finally the subject was class V MIMA NU Pliken. The results showed that in the first lesson some weaknesses were found, including the lack of participation and student achievement in the learning process. This is due to the lack of maximum learning methods used. The second learning has been increased, only still not optimal. The third learning participation and student achievement have reached the set success target to reach 100%. So that with the presence of torso media can increase active participation and student achievement in learning Natural Sciences basic competence of human respiratory organs